Five ghosts. Vol. 3, Monsters & men - Barbiere, Frank J. (Image Comics, Inc., 2015)
"After a tragic encounter with an artifact known as 'The Dreamstone,' infamous treasure hunter Fabian Gray was possessed by five literary ghosts and has been granted access to their unique abilities. These are his continuing adventures"--Cover.